The Long Shadow of Lincoln's Gettysburg Address - Peatman, Jared (Book collections on Project MUSE., 2013)
When Abraham Lincoln addressed the crowd at the new national cemetery in Gettysburg, Pennsylvania, on November 19, 1863, he intended his speech to be his most eloquent statement on the inextricable link between equality and democracy. However, unwilling to commit to equality at that time, the nation stood ill-prepared to accept the full message of Lincoln's Gettysburg Address. In the ensuing century, groups wishing to advance a particular position hijacked Lincoln's words for their own ends, highlighting the specific parts of the speech that echoed their stance while ignoring the rest. On.